A Dynamic Cyber Terrorism Framework - Rabiah, Ahmad (IJCSIS Press, 2012)
Abstract—Many nations all over the world have increased their dependency on cyberspace by maximizing the use of Information and Communication Technology (ICT). In this digital age, the concept of cyber terrorism or the use of cyberspace to carry out terrorist activities has emerged. Interestingly, there are many concepts of cyber terrorism provided by researchers, policy makers and individuals. This paper proposes a framework describing the core components of cyber terrorism. The authors have analyzed the data by using a grounded theory approach, in which the framework is drawn. The framework defines cyber terrorism from six perspectives: Target, motivation, method of attack, domain, action by perpetrator, and impact. In addition, the proposed framework provides a dynamic way in defining cyber terrorism as well as describing its influential considerations. Continued research in this area can be further conducted, which may lead to the development of strategic and technological framework to counter cyber terrorism.